Developing a national mine closure risk and opportunities atlas in GIS for South Africa - Esau, Murad (Department of Chemical Engineering, 2025)
Mining is entrenched in South Africa's history and has played a crucial role in the country's socio-economic and geopolitical development. There are currently 230 operating large-scale mines owned by 104 mining companies and hosted by 360 urban and rural communities across South Africa, comprising of approximately 6 million people – many of whom depend on mining for employment (Cole, 2024). While the impact of mine closure is well-known (Besa, et al., 2019), quantifying the extent of its impacts is not straightforward. This is particularly relevant in South Africa, where impacts may be localised due to variations in mining host community size, location, physical environmental characteristics, local infrastructure, business activity and current local economic well-being. Furthermore, determining opportunities for the post-closure phase also depends on local scenarios. South African legislation recognises the need to plan for sustainable mine closure (Mineral and Petroleum Resources Development Act, No. 28 of 2002, 2004), however there is limited tools and / or standard guidance to support this. This dissertation forms one aspect of a three-year research project funded by the Water Research Commission (WRC) aimed at producing mine closure risk ratings for all large-scale mines and a post-closure land use opportunity framework to inform and support mine closure planning. A South African Mine Closure Risk and Opportunities Atlas (‘the Atlas'), a novel analytical tool, has been developed on the basis of extensive collection of quantitative data and the visualisation thereof by means of developing a publicly available GIS tool using ArcGIS and QGIS software, with inputs from various stakeholders and industry mine closure experts following a comprehensive literature review that includes a review of existing GIS tools and methods to design such tools. It partly serves to integrate the data collected for the WRC project. Expert input informed the iterative development of the Atlas through presentations and semi-structured interviews, which guided the layout of the Atlas and the data it contains. The final result is a publicly available online and interactive Atlas which contains a comprehensive set of data that can be visualised in accordance with the identified requirements of stakeholders and experts in the field of mine closure and post-closure development planning. Through its integration of a considerable quantum of data and analytical tools, the Atlas is presented as an important tool that allows for analyses at regional scales (a key principle the South African Draft Mine Closure Strategy (2021)) as well as more local / granular scales which is useful for the identification of potential localised impacts of mine closure and opportunities for post closure land use development. The Atlas aids mine closure and post-closure land use development planning by providing all affected stakeholders with a single platform in which they can access and interpret information that can influence decision-making processes. Iterative development of the Atlas provided for a number of issues that can be addressed in further development of the Atlas, including continuous updating of the data contained in the Atlas and the inclusion of mining host community members in development processes.